Management of Temporomandibular Joint Ankylosis With Dentofacial Deformities in Children. Issue 2 (March 2018) - Jiang, Yangmei; Huang, Yuanjin; Ye, Bin; Li, Yunfeng; Zhu, Songsong
Abstract : Abstract: This retrospective study described the authors' experience in the treatment of temporomandibular joint (TMJ) ankylosis with dentofacial deformities in 18 pediatric patients during a 4-year period. These patients underwent different types of arthroplasty with condylar reconstruction, simultaneously with treatment of dentofacial deformities. Re-ankylosis was confirmed if maximal incisal opening (MIO) was <20 mm. Clinical outcomes were evaluated in terms of oral function, radiography, and medical photography. Patients were followed up for a mean time of 24.8 months. No infections, re-ankylosis, or permanent facial nerve damage were found during the hospitalization or follow-up period. All patients achieved significant improvements in MIO and oral function. The dentofacial deformities in most patients were improved to varying degrees. The results provided more useful information for the management of the pediatric patients with TMJ ankylosis and secondary dentofacial deformities. Early treatment and close follow-up play an important role in the management of these patients.